In Search of Evidence – Media and Governance in Fragile States - Stremlau, Nicole (Global Media Journal - German Edition, 2015)
This article reflects on efforts to identify evidence about the role of media in fragile states. It explores and compares findings from two research projects and focuses on some of the lessons that have emerged from these exercises as well as on the relevance of the findings for media development. While we know that media matters in areas such as conflict, reconciliation and peacebuilding, neither of the reviews of the literature found substantial evidence supporting some of the widespread claims about the importance of media, suggesting how elusive this evidence can be.